Therapeutic Endoscopic Retrograde Cholangiopancreatography for Pediatric Hepato-Pancreato-Biliary Diseases: A Systematic Review and Meta-Analysis - Sun, Rongjuan; Xu, Xiaodan; Zheng, Qipeng; Zhan, Jianghua (Frontiers in Pediatrics, 2022)
Background Hepato-pancreato-biliary (HPB) disease has different causes and types between children and adults, which has been increasingly diagnosed in the pediatric group. Endoscopic retrograde cholangiopancreatography (ERCP) has been gradually considered as a therapeutic method in adults, while in pediatric patients, there are not many reports of its usage. This systematic review and meta-analysis aims to assess the use condition of therapeutic ERCP in the management of pediatric HPB diseases. Methods This systematic literature search was conducted in the PubMed, Embase, Web of Science, and Cochrane library databases to identify all relevant articles published from inception to February 2022 that evaluated therapeutic ERCP in pediatric patients with HPB diseases. The researchers included studies in which patients were less than 18 years old and underwent therapeutic ERCP procedures. A random-effects model was used to analyze the usage rate of therapeutic ERCP procedures, procedural success rates, adverse event rates, and the rate of different therapeutic procedures. Subgroup analysis, sensitivity analysis, and meta-regression were conducted to analyze the source of heterogeneity. Results A total of 33 articles were included. After homogenization, the overall use of therapeutic interventions accounts for 77% [95% confidence interval (CI) 74–81%] of all ERCP procedures. After excluding outlier studies, the estimation success rate of the therapeutic procedure is 74% (95% CI 69–79%), and adverse event rate is 8% (95% CI 6–10%). In our study, stent placement is the most common procedure, which makes up 75% (95% CI 65–86%) of all therapeutic procedures. In addition, the usage proportion of sphincterotomy (ST), stone extraction/removal, bougienage/balloon dilation is, respectively, 46% (95% CI 39–53%), 34% (95% CI 31–38%), and 26% (95% CI 22–29%). Conclusion The ERCP procedure is gradually considered a therapeutic technique in pediatric patients, the proportion of therapeutic ERCP is 77% of total usage, which is increasing every year. Meanwhile, its success rate is relatively high. It reflects that this operation modality is promising in the treatment of HPB disorders and is gradually expanded as more branch technologies are being used. A variety of operations can be achieved through ERCP procedures, and more functions should be developed in the future. Systematic Review Registration [https://www.crd.york.ac.uk/prospero/], identifier [CRD42022302911].